Identification of a Dolabellane Type Diterpene Synthase and other Root-Expressed Diterpene Synthases in Arabidopsis - Wang, Qiang; Jia, Meirong; Huh, Jung-Hyun; Muchlinski, Andrew; Peters, Reuben J.; Tholl, Dorothea (Frontiers in Plant Science, 2016)
Arabidopsis thaliana maintains a complex metabolism for the production of secondary or specialized metabolites. Such metabolites include volatile and semivolatile terpenes, which have been associated with direct and indirect defensive activities in flowers and leaves. In comparison, the structural diversity and function of terpenes in Arabidopsis roots has remained largely unexplored despite a substantial number of root-expressed genes in the Arabidopsis terpene synthase (TPS) gene family. We show that five root-expressed TPSs of an expanded subfamily-a type clade in the Arabidopsis TPS family function as class I diterpene synthases that predominantly convert geranylgeranyl diphosphate (GGPP) to different semi-volatile diterpene products, which are in part detectable at low levels in the ecotypes Columbia (Col) and Cape Verde Island (Cvi). The enzyme TPS20 produces a macrocyclic dolabellane diterpene alcohol and a dolabellane-related diterpene olefin named dolathaliatriene with a so far unknown C6-C11 bicyclic scaffold besides several minor olefin products. The TPS20 compounds occur in all tissues of Cvi but are absent in the Col ecotype because of deletion and substitution mutations in the Col TPS20 sequence. The primary TPS20 diterpene products retard the growth of the root rot pathogen Pythium irregulare but only at concentrations exceeding those in planta. Together, our results demonstrate that divergence and pseudogenization in the Arabidopsis TPS gene family allow for structural plasticity in diterpene profiles of above- and belowground tissues.